"Mobile internet is worse than the internet; it can destroy our community": Old Order Amish and Ultra-Orthodox Jewish women's responses to cellphone and smartphone use. Issue 1 (1st January 2020) - Shahar, Rivka Neriya-Ben
Abstract: In this article I explore use patterns and perceptions of cellphone and smartphone use among Old Order Amish and Ultra-Orthodox Jewish women with participant observations, interviews, and a survey. My findings show that although they differ in their cellphone use (the Amish mostly do not use them and the Ultra-Orthodox only use those deemed to be "kosher"), they concur in their nonuse of smartphones – they see the smartphone as impure. Both view smartphones as undermining social relations and community by distracting users away from friends and family.